ATIM-42. DOUBLE-BLINDED, PLACEBO CONTROLLED PHASE 2 STUDY OF ERC1671 IN RECURRENT GLIOBLASTOMA: OS CORRELATIONS WITH INITIAL AND MAXIMUM CD4+T LYMPHOCYTE COUNT IN THE PERIPHERAL BLOOD. (11th November 2019) - Bota, Daniela; Taylor, Thomas; Xiao-Tang, Kong; Fu, Beverly; Alsharif, Mohamad; Pretto, Chrystel; Strik, Ankie; Schijns, Virgil; Stathopoulos, Apostolos
Abstract: Standard therapy for recurrent GBM is bevacizumab, a monoclonal VEGF inhibitor that targets tumor vascularization. The response to bevacizumab is transient and short-lived (4–6 months) after which patients typically develop progressive physical and mental debilitation culminating in death. ERC1671 is an allogeneic/autologous therapeutic vaccine – composed of whole, inactivated tumor cells mixed with tumor- cell lysates. The hypothesized action of ERC1671 is to potentiate the patients' immune system against the tumor. Goals of this ongoing, phase 2 study are to to determine the safety and effectiveness (over-all survival) of ERC1671 in combination with GM-CSF and cyclophosphamide as an add-on treatment to bevacizumab at the time of GBM recurrence. To date 16 recurrent bevacizumab-naïve GBM patients have been randomized to ERC1671/GM-CSF/Cyclophosphamide + Bevacizumab or Placebo + Bevacizumab. Median age is 56.5 (39–74), 5 patients (31%) are female, and average KPS is 83 (70–100). Thirteen patients are deceased and were unblinded at the time of further progression: 5 received vaccine, 7 received placebo, and 1 is non-evaluable due to discontinuation before completing 1 cycle. Median overall survival of the deceased patients treated with ERC1671 + Bevacizumab was 328 days (10.9 months), compared to 245 days (8.2 months) for patients treated with Placebo + Bevacizumab. While sparse, the data to date suggest pre-treatment and maximal CD4+T lymphocyte count in the peripheral blood correlate with OS more strongly in the ERC1671 group than in the placebo group. First clinical results for toxicity show no difference in the distribution of AEs between the Vaccine and Placebo groups, with no Gr4/Gr5 AEs in either group. The phase 2 randomized, double-blinded study is ongoing with the addition of 2 subsites.